THE IMPACT OF MEDIA WORKERS’ ATTITUDES ON THE ETHICS OF REPORTING ON MEDICALLY DIFFERENT PERSONS - Radović, Ognjen (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2017)
The way media represents the Other is the result of combination of various factors that directly or indirectly affect media workers during the production of media content about the Other. An essential and decisive factor is the personal conviction of media worker (attitudes and prejudices). Given this fact and that the media reporting on the medically different persons (MDP) is stereotypical (frame of the victim, hero or burden), it was necessary to conduct a research with reporters and editors in relation to the current level of stigma towards MDP. The research was conducted in Republic of Srpska (B&H) among reporters and editors from four leading TV stations in RS (ELTA TV, ATV, BN TV and RTRS). Using a method of in-depth interview, 19 reporters and editors responded to questions concerning: (1) their views on MDP, (2) familiarity with the specifics of various health conditions, (3) their interactions with MDP, (4) self-evaluation of reporting on MDP, (5) self-regulation and (6) applying the existing codes of ethics when reporting on MDP. The results indicate that media workers possess only basic knowledge about health differences and they primarily represent MDP on the basis of existing social stereotypes and media frames. Reporters and editors, even self-critical, tried to be socially correct, but had an ambivalent attitude and felt that self-regulation should not be used when reporting on MDP. In conclusion, it is clear that media workers use a combination of personal views on the ethics of reporting on MDP and rules of journalistic discourse, and not ethical principles and codes of reporting on the Other.